2005
DOI: 10.1002/ijc.21273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregnancy as a risk factor for breast cancer in BRCA1/BRCA2 mutation carriers

Abstract: Early age at first birth and multiparity have been associated with a decrease in the risk of breast cancer in women in the general population. We examined whether this relationship is also present in women at high risk of breast cancer due to the presence of a mutation in either of the 2 breast cancer susceptibility genes, BRCA1 or BRCA2. We performed a matched case-control study of 1,260 pairs of women with known BRCA1 or BRCA2 mutations, recruited from North America, Europe and Israel. Women who had been dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(107 citation statements)
references
References 12 publications
5
90
0
12
Order By: Relevance
“…In BRCA1 and BRCA2 carriers, parity effects may also be age dependent. While an early report suggested that parity may increase risk for early onset (o40 years) breast cancer in BRCA1 carriers (Narod, 2002a), a larger retrospective study of 1260 carrier pairs by the same group did not confirm this finding, and even observed decreased breast cancer risk in BRCA1 carriers with Xfour children (OR ¼ 0.62, 95% CI 0.41 -0.94, vs nulliparous carriers) (Cullinane et al, 2005). In BRCA2 carriers, this study found that parity caused a borderline increase in risk for breast cancer before age 50 years (OR ¼ 1.17 for each pregnancy, 95% CI 1.01 -1.36) (Cullinane et al, 2005).…”
Section: Reproductive Factorsmentioning
confidence: 86%
See 1 more Smart Citation
“…In BRCA1 and BRCA2 carriers, parity effects may also be age dependent. While an early report suggested that parity may increase risk for early onset (o40 years) breast cancer in BRCA1 carriers (Narod, 2002a), a larger retrospective study of 1260 carrier pairs by the same group did not confirm this finding, and even observed decreased breast cancer risk in BRCA1 carriers with Xfour children (OR ¼ 0.62, 95% CI 0.41 -0.94, vs nulliparous carriers) (Cullinane et al, 2005). In BRCA2 carriers, this study found that parity caused a borderline increase in risk for breast cancer before age 50 years (OR ¼ 1.17 for each pregnancy, 95% CI 1.01 -1.36) (Cullinane et al, 2005).…”
Section: Reproductive Factorsmentioning
confidence: 86%
“…While an early report suggested that parity may increase risk for early onset (o40 years) breast cancer in BRCA1 carriers (Narod, 2002a), a larger retrospective study of 1260 carrier pairs by the same group did not confirm this finding, and even observed decreased breast cancer risk in BRCA1 carriers with Xfour children (OR ¼ 0.62, 95% CI 0.41 -0.94, vs nulliparous carriers) (Cullinane et al, 2005). In BRCA2 carriers, this study found that parity caused a borderline increase in risk for breast cancer before age 50 years (OR ¼ 1.17 for each pregnancy, 95% CI 1.01 -1.36) (Cullinane et al, 2005). In a case-only study, young age at first pregnancy delayed onset of breast cancer in carriers (King et al, 2003), and a retrospective study of 1601 carriers found that in women over 40 years of age, each full-term pregnancy reduced breast cancer risk by 14% (95% CI 6 -22%).…”
Section: Reproductive Factorsmentioning
confidence: 86%
“…However, many type of fruits for example orange and lemon have B and C vitamins and antioxidant elements that may decrease or prevente BC incidences (Blount, 2002;Azizi, 2003;Cullinane, 2005;Greene, 2006). Our incidences and use of fruits that is in agreement with some studies (Blount, 2002;Azizi, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of pregnancy on hereditary breast cancer risk appears to differ for BRCA1 and BRCA2 carriers. In a large matched case-control study, Cullinane et al (2005) reported that the risk of breast cancer did not decrease with pregnancy in BRCA1 carriers until four births were reached, after which there was only a modest protective effect. However, among BRCA2 carriers, there was a statistically significant increase in breast cancer risk with each additional pregnancy (OR ¼ 1.17, 95% CI: 1.01-1.36; P ¼ 0.03).…”
Section: Pregnancymentioning
confidence: 99%